2022
DOI: 10.1108/aa-04-2021-0045
|View full text |Cite
|
Sign up to set email alerts
|

Research on robust adaptive sliding film fault-tolerant control under nonlinear distortion of signal transmission in amorphous flat air-to-ground wireless ad-hoc network system

Abstract: Purpose To solve the above problems and ensure the stability of the ad hoc network node topology in the process of wireless signal transmission, this paper aims to design a robust adaptive sliding film fault-tolerant controller under the nonlinear distortion of signal transmission in an amorphous flat air-to-ground wireless ad hoc network system. Design/methodology/approach This paper designs a robust adaptive sliding film fault-tolerant controller under the nonlinear distortion of signal transmission in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Next, reference (Wang et al, 2017(Wang et al, , 2020(Wang et al, , 2023d(Wang et al, , 2023e, 2023c(Wang et al, , 2023b(Wang et al, , 2023a(Wang et al, , 2021 gives the failure mode of the internal actuator of the system shown in equation ( 3):…”
Section: Design Of Neural Network-based Direct Robust Adaptive Non-fr...mentioning
confidence: 99%
See 4 more Smart Citations
“…Next, reference (Wang et al, 2017(Wang et al, , 2020(Wang et al, , 2023d(Wang et al, , 2023e, 2023c(Wang et al, , 2023b(Wang et al, , 2023a(Wang et al, , 2021 gives the failure mode of the internal actuator of the system shown in equation ( 3):…”
Section: Design Of Neural Network-based Direct Robust Adaptive Non-fr...mentioning
confidence: 99%
“…Referring to the literature (Wang et al , 2017, 2020, 2023d, 2023e, 2023c, 2023b, 2023a, 2021), in this paper, the amorphous flattened air-ground wireless self-assembled network system is equated to the uncertain system state space model shown in equation (1): …”
Section: Overall System Frameworkmentioning
confidence: 99%
See 3 more Smart Citations